Pengaruh Penambahan Limbah Lumpur Penyamakan Kulit Pada Sifat Fisis Tanah Lempung - Athaya Zhafirah; Arin Febriani Putri (Institut Teknologi Garut, 2024)
Tannery sludge waste is solid waste produced by the leather tanning industry. This waste is B3 waste because it can cause itching on the skin, health problems and give off an unpleasant odor. However, this waste also contains the same compounds as cement, namely iron and aluminum, so it can be used as a substitute material for clay soil with the aim of increasing the soil's bearing capacity. Clay soil is considered poor soil if it is to be used as the basis for construction. Therefore, research was carried out on the physical properties of clay soil mixed with tannery mud waste. The method used is experimental, where the physical properties of clay soil are tested, consisting of water content, bulk density, specific gravity, sieve analysis, and Atterberg limit, plus a mixture of tannery mud waste in proportions of 0%, 25%, 50%, and 75%. % of soil weight. The results of the research showed that clay soil with the addition of tannery sludge waste resulted in a decrease in water content; increase in unit weight and specific gravity; the proportion of fine grains decreases and coarse grains increase; as well as an increase in the plasticity index.